2014
DOI: 10.1177/0269215514525059
|View full text |Cite
|
Sign up to set email alerts
|

Intensive, progressive exercise improves quality of life following lumbar microdiskectomy: a randomized controlled trial

Abstract: An intensive, progressive exercise program combined with education increases quality of life in patients who have recently undergone lumbar microdiskectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…In the literature, exercise has been reported to have benefits in the improvement of the physical and psychological aspects of health‐related quality of life besides providing better management of pain and disability (Garber et al, 2011; McAuley et al, 2012). Consistent with previous study results (Beneck et al, 2014; Mobbs et al, 2016; Selkowitz et al, 2006), the current study findings have shown that there was a significant improvement in the physical (physical role and pain) and mental (energy and vitality, mental health and social functionality) health components of the quality of life of the patients in the intervention group compared with the control group, where physical activity had a direct relationship with those components of quality of life. These findings may be the result of pain and disability decreasing with increasing physical activity.…”
Section: Discussionsupporting
confidence: 93%
“…In the literature, exercise has been reported to have benefits in the improvement of the physical and psychological aspects of health‐related quality of life besides providing better management of pain and disability (Garber et al, 2011; McAuley et al, 2012). Consistent with previous study results (Beneck et al, 2014; Mobbs et al, 2016; Selkowitz et al, 2006), the current study findings have shown that there was a significant improvement in the physical (physical role and pain) and mental (energy and vitality, mental health and social functionality) health components of the quality of life of the patients in the intervention group compared with the control group, where physical activity had a direct relationship with those components of quality of life. These findings may be the result of pain and disability decreasing with increasing physical activity.…”
Section: Discussionsupporting
confidence: 93%
“…15,16,24 Blinding of clinicians and outcome assessors in certain studies was of a concern. 15,18,20,31 Inadequate blinding of researchers and outcome assessors could have increased the chances of detection bias. 3,15,32 Inconsistencies with regard to allocation concealment and sequence generation were also not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 studies included, only 5 reported on the occurrence of adverse effects. [16][17][18]27,31 As shown in A great amount of variability was also found with regard to exercise dosage, since programmes were individualized to suit the specific population groups in question. The frequency of training sessions per week ranged from 2 to 5, with three sessions per week being the most common.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations